Effects of production conditions on the properties of limestone briquettes aimed for acid soil liming - Jovanović Vladimir; Nišić Dragana; Milisavljević Vladimir; Todorović Dejan; Radulović Dragan; Ivošević Branislav; Milićević Sonja (Hemijska Industrija, 2022)
This paper presents the results of experiments performed to determine how the quantity of the binder (bentonite) and the parameters of the laboratory roll press affect the quality of the briquettes obtained from limestone powder. These experiments aim to examine the conditions in which limestone briquettes are formed and to determine their use for agricultural purposes. During the experiments various mass fractions of bentonite was added to limestone (from 1 to 10 %), while the force of roll press drums ranged from 2 to 25 kN. The briquettes have been tested by applying scanning electron microscopy (SEM), differential thermal and thermo-gravimetric (DTA/TG) analyses, X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR). Bentonite distribution was found to be uniform within the compact briquette structure. Formation of new compounds was not evidenced. The experiments also demonstrated that during briquetting, limestone properties remain unchanged, the changes are only physical, water solubility is not reduced, mechanical properties (impact resistance, compressive strength and abrasion resistance) are satisfactory by the transport and storage terms if the binder mass fraction is over 5% and the briquetting force exceeds 10kN and finally there is no loss due to wind dispersal during application. The only downside of the “green” briquettes obtained is the time required for their complete disintegration if totally immersed in water.